2021
DOI: 10.3389/fgene.2021.672904
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Genes in Lung Adenocarcinoma: Prognostic Signature and Immune, Drug Resistance, Mutation Analysis

Abstract: Graphical AbstractFerroptosis genes in lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 101 publications
3
35
0
Order By: Relevance
“…It is also associated with immune cell inflammation (31). Consistently, a very recent study also suggested that increased expression of PEBP1 is related to survival status in lung adenocarcinoma patients (32). In our study, however, only LPIN1 is found to be correlated with survival status in sepsis.…”
Section: Discussionsupporting
confidence: 86%
“…It is also associated with immune cell inflammation (31). Consistently, a very recent study also suggested that increased expression of PEBP1 is related to survival status in lung adenocarcinoma patients (32). In our study, however, only LPIN1 is found to be correlated with survival status in sepsis.…”
Section: Discussionsupporting
confidence: 86%
“…When SystemXc- is blocked, glutamate and cystine cannot be exchanged, resulting in intracellular glutamate accumulation, reduced glutathione synthesis, and reduced GPX4 activity, which ultimately leads to ferroptosis ( 58 ). Further, the inhibition of SLC3A2, a ferroptosis suppressor gene, promotes ferroptosis in tumor and normal cells ( 57 , 59 ), and hence, its upregulation is associated with poor prognosis of cancer ( 60 ). FTH1 (Ferritin heavy polypeptide 1) is an important component of ferritin.…”
Section: Discussionmentioning
confidence: 99%
“… 44 The proportion of T cells decreased in the lungs of current smokers and patients with COPD, whereas the proportion of macrophages increased. 45 In our study, we uncovered the immune infiltration status in patients with COPD compared with normal controls. Monocytes were the majority of immune cells in both groups and increased prominently in COPD group.…”
Section: Discussionmentioning
confidence: 99%